Famous Women Artists Who Shattered Gender Norms and Redefined Art - Islomova Sevinch Botirjon qizi (Academia One Publishing, 2023)
This article explores the contributions of famous women artists who defied prevailing gender norms and transformed the landscape of art. It sheds light on how these pioneering women challenged societal expectations, transcended traditional roles, and reshaped the art world. Through their exceptional talents and unyielding determination, these artists left an indelible mark on the history of art, inspiring future generations to break free from gender constraints and create on their terms.
Keywords: Women artists; Gender norms; Art history